European telecommunications law: Unaffected by globalisation? - Christoph Engel (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2002)
Globalisation can mean one of four things: a considerable degree of regulatory competition; a geographically relevant market transgressing national and regional borders; the transfer of significant regulatory power to supranational entities; the public perception that nation states have lost a remarkable degree of regulatory independence. Any of these four definitions can be applied to the shifting relationship between national and European regulatory powers as well. Accordingly, the clash between Europeanisation and globalisation opens up a host of exiting theoretical hypotheses. This paper elaborates on the options, and tests them empirically in the field of telecommunications, using the new regulatory framework proposed by the European Commission as evidence. The result is sobering. Signs of Europeanisation abound, while there is hardly an unequivocal sign of globalisation. Strategic neglect seems the most plausible explanation. The paper concludes by demonstrating why this is a political, but not a legal problem.
Keywords: 330; Telekommunikationsrecht; EU-Wirtschaftsrecht; Globalisierung; Telekommunikationspolitik; International; EU-Staaten; Policy-Ansatz